Large morphological transitions underlie exceptional shape diversification in an adaptive radiation - Katherine B. Starr; Emma Sherratt; Thomas J. Sanger (Scientific Reports)
Abstract Adaptive radiations are characterized by an increase in species and/or phenotypic diversity as organisms fill open ecological niches. Often, the putative adaptive radiation has been studied without explicit comparison to the patterns and rates of evolution of closely related clades, leaving open the question whether notable changes in evolutionary process indeed occurred at the origin of the group. Anolis lizards are an oft-used model for investigating the tempo and mode of adaptive radiations. Most of the prior research on the diversification of Anolis morphology has focused on the post-cranium because of its significance towards subdivision of the arboreal habitat. But the remarkable diversity in head shape in anoles has not been as thoroughly investigated. It remains unknown whether the tempo or mode of head shape diversification changed as anoles diversified. We performed geometric morphometric analysis of skull shape across a sample of 12 Iguanian families (110 species), including anoles. Anolis lizards occupy a unique area and a wider region of morphological space compared to the 11 other families examined. We did not find a difference in the evolutionary rate of head shape diversification between anoles and their relatives. Rather, the extraordinary amount of skull diversity arose through a distinct mode of evolution; anoles moved into novel regions by relatively large morphological transitions across morphological space compared to their relatives. Our results demonstrate that traits not directly tied to the adaptive shift of a lineage into unique ecological spaces may undergo exceptional patterns of change as the clade diversifies.